Throughput Enhancement of the RIPEMD-160 Design Using the Unfolding Transformation Technique - Shamsiah, Suhaili; Takahiro, Watanabe; Norhuzaimin, Julai (Journal Management System, 2021)
Abstract: Many cryptographic applications use RIPEMD-160 hash functions, such as digital signatures, Hash Message Authentication Code (HMAC), and other data security applications. The suggested RIPEMD-160 designs are as follows: RIPEMD-160 iterative design, RIPEMD-160 unfolding with factor two, and RIPEMD-160 unfolding with factor four. These methodologies were applied to RIPEMD-160 designs in order to evaluate the inner structure of the design in terms of area, maximum frequency, and throughput. In this project, the RIPEMD-160 hash function was implemented with a high throughput utilising an unfolding transformation technique with a factor of four. The throughput of RIPEMD-160 unfolding design has been increased. The goal of the project is to improve the throughput of RIPEMD-160. The throughput of RIPEMD-160 was increased to around 1753.50 Mbps by applying the unfolding transformation factor four approach. When RIPEMD-160 unfolding with factor four designs is compared to other RIPEMD-160 designs, the percentage of performance to area ratio increases by 1.51%. In comparison to alternative designs, the results suggest that the proposed designs perform the best. ModelSim Altera-Quartus II simulation results were used to prove the accuracy of the RIPEMD-160 designs in terms of functional and timing simulations.